Optimal Portfolio: what or when? Various approach to achieve “Optimal” portfolio / Budi Purwanto … [et al.] - Purwanto, Budi; Dwi Hardono, Edryoko; Karunia Amanah, Nanda; Respati, Prima (Faculty of Accountancy, 2019)
Various approaches can be applied to obtain an optimal portfolio, and therefore produce a variety of different "optimal results". The question arises, the optimal portfolio is actually a stable equilibrium which in the long run can be a benchmark, or a short-term conditional combination that has no permanent equilibrium? This paper aims to evaluate several approaches to optimal portfolio formation by considering several factors as determinants. The objectives are: 1) to form an optimal portfolio based on Markowitz's modern portfolio theory as a benchmark; 2) develop alternative optimal portfolios based on sectoral, regional and temporal approaches; 3) form optimal portfolio with certain moral and informational restrictions; 4) identify the effects of contrarian and rebalancing strategies; and 5) evaluating the most reasonable concept as an approach to obtain an optimal portfolio. Methods Markowitz, Single Index Model, data listing BEI 2011-2019. Therefore this study intends to make an optimal portfolio followed by a series of confident sectoral, regional, temporal, moral and rebalancing strategies with some combination of optimization’s method. The results of this study is sufficient to prove the that the better quality of portfolio have a better value at risk portfolio.